A nação vai à província: do romantismo ao modernismo no Ceará - Marques, Rodrigo de Albuquerque (2016)
This thesis aims at analyzing the dynamics of the National literary system according to Antonio Candido‘s terms, from a distant province far from big hegemonic centers of the country, embracing the periods of 1856 to 1930. It focuses on observing how such movements as Romanticism, Naturalism and Modernism structured themselves within the historical particularities which were configuring the field of literature in Ceará. An amount of poetic and romantic production from the above mentioned period, which is somehow closely connected to local circumstances, was selected in this thesis; however, such production was, at the same time, integrated 18th century assumptions concerning nationalism and, afterwards, if was attuned to more conservatives tendencies of Modernism. As opposed to the literary corpus, it is used a range of another sources, such as letters, popular poems, maps, articles, statistics, memoirs etc. to the purpose of supplying the reader with a more accurate dimension regarding the place of literature in the whole of the culture of the region and also of the country.